The Effect of EDM with external magnetic field on surface roughness of stainless steel - Khan, Ahsan Ali; Ndaliman, Mohammed Baba; Mohammad , Yeakub Ali; Al-Falahi, Muath D.; Ibrahim, Haazin A.; Mustapa, Mohad S. (2013)
During electro-discharge machining (EDM), debris particles are generated in the machining gap from the eroded materials. If they are not quickly removed, arcing would occur, and this reduces the machining efficiency. The introduction of external magnetic field (EMF) is a research innovation which tries to facilitate quick removal of this debris away from the machining gap. In this paper, the influence of EMF on the surface roughness of SUS 304 stainless steel is reported. The investigation was conducted under the current intensity range of 2.5 to 6.5A and duty factor of 40 to 56%. Results indicate that the introduction of magnetic field in EDM is effective within the current range of 2.5 to 4.5A. Under these currents, the EDM conducted with magnetic field at 50% duty factor produced lowest surface roughness of about 2.4μm. At higher currents, however, the magnetic field effect becomes minimal as rougher surfaces were obtained with it. The highest duty factor of 56% also produced the roughest surfaces in the two machining schemes under the highest peak current.